PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF IMPLEMENTING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF MILITARIZED HIGHER EDUCATION INSTITUTIONS - Abdurakhmonov Zafar Botirovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The article presents a theoretical and analytical examination of the pedagogical and psychological features of the use of artificial intelligence technologies in the educational process of militarized higher education institutions. Based on the synthesis of contemporary domestic and international research, the study reveals the specificity of artificial intelligence application under conditions of military discipline, regulatory control, and heightened personal responsibility of learners. Particular attention is given to the influence of artificial intelligence on learning motivation, critical thinking, and independent decision-making. The article substantiates the necessity of regulated and pedagogically controlled use of artificial intelligence as a supplementary educational tool within the system of military education.